CAMELLIA HOABINHENSIS (THEACEAE: SECT. CHRYSANTHA), A NEW YELLOW-FLOWERED SPECIES FROM NORTHERN VIETNAM - Van Hoi Quach; Ninh Tran; Van Dung Luong; Thanh Truong Hoang; Shuichiro Tagane; Van The Pham (Tạp chí Khoa học Đại học Đà Lạt, 2023)
A new species, Camellia hoabinhensis (section Chrysantha, Theaceae), is described and illustrated based on specimens collected from a lowland forest on limestone hills in Hoa Binh Province, northern Vietnam. The species is characterized by its small habit to 4.5 m tall, large flowers 9.0–9.5 cm in diameter with 18–19 light yellow petals, and hairy filaments, ovaries, and styles. A comparison of the new species with similar species, C. euphlebia, C. impressinervis, C. phanii, and C. velutina, is provided. The IUCN conservation status of the proposed species is Data Deficient (DD).